1997
DOI: 10.1001/archinte.1997.00440410105012
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Zinc Salts Lozenges and the Common Cold

Abstract: Despite numerous randomized trials, the evidence for effectiveness of zinc salts lozenges in reducing the duration of common colds is still lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…These studies appear to have addressed many of the criticisms of previous studies of the effect of zinc on common-cold symptoms [15,16]. Although the placebo treatment was not matched in this study, the responses of the volunteers suggest that the at California Institute of Technology on June 22, 2015 http://cid.oxfordjournals.org/ Downloaded from study was adequately blinded and that neither unpalatable taste nor the occurrence of adverse events should have affected the results of the study.…”
Section: Discussionmentioning
confidence: 67%
“…These studies appear to have addressed many of the criticisms of previous studies of the effect of zinc on common-cold symptoms [15,16]. Although the placebo treatment was not matched in this study, the responses of the volunteers suggest that the at California Institute of Technology on June 22, 2015 http://cid.oxfordjournals.org/ Downloaded from study was adequately blinded and that neither unpalatable taste nor the occurrence of adverse events should have affected the results of the study.…”
Section: Discussionmentioning
confidence: 67%
“…[26][27][28] The ingestion of coins by psychiatric patients also has been reported as a source of increased zinc ingestion (leached from the coins) and subsequent copper deficiency. 25,29,30 Since 1982, pennies have been composed of 97.6% zinc and 2.4% copper; other US coins do not contain zinc.…”
Section: Discussionmentioning
confidence: 99%
“…Using the outcome of cold symptoms after 7 days, a meta-analysis of eight clinical trials of zinc salt lozenge for the treatment of common cold did not find a significant benefit. 34 In contrast, clinical trials showed that zinc effectively and significantly shortened the duration of the common cold when it was administered within 24 h of the onset of symptoms. 35 Vitamin C may have a small role in preventing the common cold, especially in persons exposed to brief periods of severe physical activity or cold environments, 36 37 but has no apparent effect on the duration or severity of symptoms.…”
Section: Mucolytic Agentsmentioning
confidence: 99%